1991
DOI: 10.3171/jns.1991.75.3.0364
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of limbic epilepsy associated with extrahippocampal lesions: the problem of dual pathology

Abstract: The authors present their review of 178 patients who underwent en bloc temporal lobectomies as surgical treatment for intractable epilepsy. Hippocampal cell density was quantitatively analyzed and the histology of the anterior temporal lobe was reviewed. Fifty-four patients (30.3%) had evidence of extrahippocampal lesions in addition to neuronal cell loss within the hippocampus (the dual pathology group). The pattern of cell loss was analyzed in the remaining 124 cases (69.7%) with no extrahippocampal patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
2
7

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(130 citation statements)
references
References 38 publications
(3 reference statements)
4
116
2
7
Order By: Relevance
“…Nevertheless, some authors hypothesized that patients with treatment-refractory epilepsy and Ammon's horn sclerosis are at reduced risk for psychosis (45,47,72). Patients with a history of febrile convulsions exhibit specific cell loss in the CA fields of the hippocampus (82,83). This great reduction in cells of these areas might provide some protection against overactivity of hippocampal neurons induced by interictal BEHA VIORA L, PSYCHO TIC, AND ANXIETY DISORDERS s7 epileptiform activity and related to development of delusions (45).…”
Section: Febrile Convulsions and Psychosismentioning
confidence: 99%
“…Nevertheless, some authors hypothesized that patients with treatment-refractory epilepsy and Ammon's horn sclerosis are at reduced risk for psychosis (45,47,72). Patients with a history of febrile convulsions exhibit specific cell loss in the CA fields of the hippocampus (82,83). This great reduction in cells of these areas might provide some protection against overactivity of hippocampal neurons induced by interictal BEHA VIORA L, PSYCHO TIC, AND ANXIETY DISORDERS s7 epileptiform activity and related to development of delusions (45).…”
Section: Febrile Convulsions and Psychosismentioning
confidence: 99%
“…27,28,43 The presence of dual pathology in patients with MTS has been well described in the literature. Some authors have found a 15%-30% incidence of this type of dual pathology in their series of patients with TLE.…”
Section: Reasons For Failure Of Temporal Lobe Resectionmentioning
confidence: 90%
“…Some authors have found a 15%-30% incidence of this type of dual pathology in their series of patients with TLE. 27,41 In this situation both the dysplastic temporal neocortex and the sclerotic hippocampus can be epileptogenic. It appears that the contribution of the hippocampus to seizure generation corresponds to the degree of hippocampal pathology, whereas even mild forms of cortical dysplasia can be epileptogenic.…”
Section: Reasons For Failure Of Temporal Lobe Resectionmentioning
confidence: 99%
“…The occurrence of 'dual pathology' in patients with TLE was initially proposed by Rush and Morrell [7] and Lévesque et al [8]. Dual pathology does not merely indicate the anatomical coexistence of HS with an extrahippocampal lesion, but also pathophysiological mechanisms such as the kindling phenomenon and secondary hippocampal epileptogenesis [9,10,11,12].…”
Section: Discussionmentioning
confidence: 99%